Exposing Covert Border Enforcement: Why Failing to Shift the Burden of Proof in Pushback Cases is Wrong - Baranowska, Grażyna (European Convention on Human Rights Law Review, 2023)
The paper analyses how the European Court of Human Rights (ECtHR or the Court) assesses evidence when states conceal border practices, such as pushbacks, comparing the Court’s approach in those cases to that in enforced disappearance cases. In both types of cases, states deny that the conduct – which would have violated human rights – has taken place and provide neither the applicants nor the Court with evidence. While surface examination of the relevant case law could suggest that the ECtHR shifts the burden of proof in the same way in both sets of cases, I demonstrate that the Court expects applicants in covert border enforcement cases to provide stronger evidence, which is then labelled as prima facie evidence. I argue that the burden of proof should be shifted in the same way in both scenarios, as the position of the victims and the availability of evidence is strikingly similar.
CRIS-Team Scopus Importer:2024-08-12
Keywords: border violence; burden of proof; enforced disappearance; prima facie evidence; pushback; shifting the burden of proof